Multi Phase Center Processing of Ice Sounding Radar Signals for Across Track Surface Clutter Cancellation: Validation Test Report - Villano, Michelangelo; Nannini, Matteo; Prats, Pau; Scheiber, Rolf (2013)
ESA’s POLarimetric Airborne Radar Ice Sounder demonstrator (POLARIS) - build and operated by the Technical University of Denmark (DTU) - operates at P-band and features a multi-phase-center antenna for the purpose of surface clutter suppression. The first data suitable for the development and demonstration of suitable surface clutter cancellation methods were acquired in February 2011 during the IceGrav campaign in Antarctica. The purpose of the present study is to investigate and compare different methods for POLARIS surface clutter cancellation and to implement a Processing Tool to augment the along-track POLARIS processor developed by ESA, thus improving bedrock detectability. The present technical note concerns the validation and test of the developed algorithms implemented into a Processing Tool for multi-phase center surface clutter cancellation (in the following referred to as MPC Processing Tool). The activities documented in this technical note are divided into two major parts:  Validation and test results with simulated data,  Validation and test results with real POLARIS data. The validation methodology and definition of test data is according to the Validation and Test Methodology as defined in technical note DD-2 of the present project.